PENGGUNAAN DAUN UBI KAYU (Manihot esculenta) DENGAN PENGOLAHAN BERBEDA TERHADAP PERFORMA KAMBING PERANAKAN ETAWA JANTAN - Okni Winda Artanti; Muhammad Ridla; Lilis Khotijah (JURNAL ILMIAH PETERNAKAN TERPADU, 2019)
The objective of this experiment was to evaluate the effect of fresh, dried or silage cassava leaf to the performances of male Etawa Crossbreed (EC) goats. Fourteen male EC goats (grouping based on body weight with a weight range K1: 19-20 kg; K2: 20-21 kg; K3: 21-22 kg; K4: 22 kg) were allocated in housed individually throughout 90-day trial duration (14 days for animal's adaptation to the experimental diets and 7 days of faeces collection). Experimental design was randomized complete block design consisted of 3 treatments and 4 replications: concentrate + fresh cassava leaf (T0); concentrate + dried cassava leaf (T1); and concentrate + silage cassava leaf (T2). Concentrat was given at level of 50% (3% BW) and forage was given ad libitum respectively for each treatments. Variables observed were feed intake, digestibility, body weight gain, and feed efficiency. Data were analyzed using analysis of variance (ANOVA), if there were significant effect of treatments were continued using Duncan multiple range test. The results of this experiment showed that the processing of cassava leaf increased on dry matter intake, crude protein, total digestible nutrient (TDN), digestibility, body weight gain, and feed efficiency. The conclusions were processing of cassava leaves improved the consumption and digestibility of male EC goats and the treatment of cassava leaf silage had the best feed efficiency. Keywords: Cassava Leaf, Performance, Digestibility, Male Etawa Crossbreed Goat.